Social commentary, subaltern voices and the alternative medium of Zimdancehall music: unpacking the music of Winky D and Sniper Storm - Ureke, Oswelled; Washaya, Yollanda (Routledge, 2021)
The article explores the subject of Zimbabwean dancehall (Zimdancehall) music, a contemporary genre whose local popularity is on the rise, particularly among urban youths. Zimdancehall is infamous for its sometimes ‘dirty’ lyrics and the stereotyped ‘ghetto’/dancehall culture of drug and alcohol abuse, sex and rebelliousness that pervade its creation and consumption. This article critically analyses selected songs by two of the most popular and established Zimdancehall musicians, Winky D and Sniper Storm. Their music shows that beyond the party themes and colloquial language employed in Zimdancehall, the genre embodies deep commentary and consciousness on topical issues affecting society. It is also shown in this article that Zimdancehall, as a form of popular culture, has positioned itself as an alternative medium through which youths, as a subaltern group, speak back to power, pointing out their daily tribulations, while at the same time deconstructing the hegemony of the elites who wield political and economic authority.